Institutional Variables as Determinants of Lecturer's Job Performance in Kwara State Colleges of Education - Adeleke Towobola, Abubakar; Moshood Oyewale, Kunle; Sunday Olaif, Adeseko; Kadir Abdulrahman Babamole; Adeleke Adeoye, Moses (Manajer Pendididikan, 2024)
Institutional variables are indispensable tools for attaining educational goals in Colleges of Education. This study examined institutional variables as determinants of lecturers’ job performance in Kwara State Colleges of Education. The study adopted a descriptive survey of correlational type. Two research questions and one hypothesis were raised to guide the study. The population of the study consisted of two hundred and fifteen respondents using Research Advisors. The researcher instruments used were titled Institutional Variables Questionnaire (IVQ) and Lecturers’ Job Performance Questionnaire (LJPQ) were used to collect data for the study. Mean, Standard deviation and Pearson Product-Moment Correlation Statistics were used to analyze the data. The findings of the study revealed that the level of lecturers’ job performance was high in Kwara State Colleges of Education. There was a significant relationship between relationship between institutional variables and lecturers’ job performance in Kwara State Colleges of Education. It was recommended among others that the management of Kwara State Colleges of Education should supply essential and modern library facilities for lecturers and students so that effective teaching and learning will be improved upon.